2007
DOI: 10.1002/hep.1840030113
|View full text |Cite
|
Sign up to set email alerts
|

Arteriohepatic Dysplasia. II. Hepatobiliary Morphology

Abstract: Five children were noted to have arteriohepatic dysplasia (Alagille's syndrome) between 3 and 7 months of age. Prior to diagnosis, four underwent Kasai procedures after intraoperative cholangio‐grams failed to demonstrate patency of the extrahepatic bile ducts. In three patients, a focal proximal hypoplasia of the common hepatic duct was demonstrated with fibrosis and increased vascularity. Hypoplasia of the gallbladder occurred in two patients. Changes were observed in the porta hepatis. Eighty to 208 /tm bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 14 publications
(13 reference statements)
0
28
0
Order By: Relevance
“…The inability to do this during the postnatal period generates the paucity of bile ducts in ALGS liver. Consistent with this, the extent of bile duct paucity varies with location in ALGS liver (7,52,53), and is most severe in the liver periphery (56). Based upon analysis of ALGS liver tissue, it has been proposed that altered Notch signaling impairs the formation of the distal branches of the biliary tree during the postnatal period in ALGS liver (57).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The inability to do this during the postnatal period generates the paucity of bile ducts in ALGS liver. Consistent with this, the extent of bile duct paucity varies with location in ALGS liver (7,52,53), and is most severe in the liver periphery (56). Based upon analysis of ALGS liver tissue, it has been proposed that altered Notch signaling impairs the formation of the distal branches of the biliary tree during the postnatal period in ALGS liver (57).…”
Section: Discussionmentioning
confidence: 71%
“…ALGS patients are born with an intact biliary system (51), but the ratio of bile ducts to liver tissue quickly declines with age after birth, which leads to cholestasis and presentation with ALGS liver disease (7,52,53). The proximal branches of the biliary tree are formed in embryonic liver from a single layer of bipotent precursor cells that surround the portal vein (the ductal plate), which are progressively remodeled to generate intrahepatic bile ducts (54), and this requires an interaction with surrounding mesodermal tissues (55).…”
Section: Discussionmentioning
confidence: 99%
“…33 Li et al 23 and Oda et al 31 demonstrated that mutations in the Jagged1 gene can cause AGS. 6,16 Analyses of sequential liver biopsies have clearly shown that the bile duct/portal tract ratio declines with increasing age, with a concomitant increase in the severity of cholestasis. 35 The most prominent and nearly constant feature of AGS is intrahepatic bile duct paucity, which is defined as a bile duct/portal tract ratio less than 0.5.…”
mentioning
confidence: 99%
“…This gene encodes a transmembrane protein that functions as a ligand in the developmentally important Notch-pathway, which contains four receptors (Notch1 to Notch4), and it has been suggested that haploinsufficiency is the mechanism of disease causation. 6,8,16 The finding that bile duct damage is not a prominent, consistent feature in liver biopsies 6,8 strongly argues against destruction as the mechanism of bile duct disappearance. 33 The pathogenesis of this paucity is currently not well understood.…”
mentioning
confidence: 99%
“…There are numerous publications describing the histopathological features of the liver in AGS Dahms et al 1982 ;Hadchouel 1992 ;Hashida and Yunis 1988 ;Kahn et al 1983 ;Witzleben 1982 ). Though Alagille based his original diagnosis of the syndrome on a BD/PT ratio less than 0.5, the presence and extent of bile duct paucity vary, largely as a result of the different ages of the patients at the time of biopsy Dahms et al 1982 ;Emerick et al 1999 ;Hadchouel 1992 ;Hashida and Yunis 1988 ;Kahn et al 1983 ;Quiros-Tejeira et al 1999 ;Witzleben 1982 ).…”
Section: Histopathology Of the Liver In Agsmentioning
confidence: 99%